Insult and the Making of the Gay Self - Eribon, Didier (Book collections on Project MUSE., 2004)
Didier Eribon reflects on 'the gay question' & the creation of gay identities. In an age when it is claimed that being gay has been reduced to 'a lifestyle' Eribon argues that gay male politics, social life & culture should properly be seen as a transformative response to an oppressive social order.